Reconfiguring the battery innovation landscape - Silva, J. (2023)
Batteries are critical for energy transition strategies. This paper offers a comprehensive assessment of the trends and developments of battery innovation. Over 700,000 patents from the period of 2005-2019 are compiled and analyzed. Leading patent applicants and countries of origin are identified. Major patent applicants are mostly large East Asian companies, while Japan and South Korea are the leading countries followed by the US, Germany, and China. Different battery designs, the main battery components, and interactions with other clean technologies are examined. Based on the operative definitions for incremental/radical and product/process innovations, a battery innovation typology is set forth. Main findings are that patenting in batteries has risen robustly and lithium-ion is the most vibrant technology; the lead-acid set-up maintains consistent innovation activity, lithium-sulfur and flow batteries are the most notable emerging technologies; electrodes are the most salient battery component, followed by electrolytes, separators, and cell housing; the most significant interactions of batteries with clean energy technologies are between battery charging and photovoltaic energy as well as between battery charging and electric vehicles. Incremental innovation represents more than half of patents, while product innovation represents approximately 70% of total patents.